UPAYA MENINGKATKAN AKTIVITAS HASIL BELAJAR SISWA PADA MATERI PECAHAN DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING KELAS IV SDN SUMUR 03 - Pukjiwati Pukjiwati (Universitas Muria Kudus, 2017)
The purpose of this study was to determine whether there is a science learning outcomes in Operation Count Fraction In Problem Solving in Elementary School fourth grade Sumur 03, Subdistrict Cluwak, Pati. In the first semester of the school year 2016/2017 This research is a classroom action research to solve the problem of whether the approach CTL can improve student learning outcomes. PTK lasted until 2 cycles, each cycle consisting of (1) planning, (2) actions, (3) of observation, and (4) reflection. The fourth connection is regarded as one cycle. Collection and use of technical documentation, observation and testing, data collection tools such as document journal learning, observation sheets and test items. Data analysis using descriptive comparative by comparing baseline data of the first cycle and the second cycle data followed by reflection. The study of 18 students learning the standard minimum value of 65, which means that students who have reached a value above 65 otherwise been completed. Furthermore, students who achieve a value of less than or equal to 65 otherwise unresolved in learning and need to get improvements in learning. From the research results at the end of the lesson formative tests turned out of 18 students who achieve grades above completeness only 8 students, if diprosentase students who otherwise completed only 35%. So unresolved reached 65%. The conclusion of the research approach CTL can improve the quality of student learning outcomes of the Mathematics of Operations Troubleshooting Count Fraction in fourth grade elementary school Sumur 03, District Cluwak, Pati regency, through the medium of learning and teaching.